Die doel, taak en terrein van die opvoedkunde soos beoefen aan die PU vir CHO (1935-1985) - Walt, J. L. van der (Koers, 1986)
In agreement with the method of historical weight it was hypothesized that the academic leaders of a Faculty of Education (i.e . the five deans who served in the PU for CHE's Faculty of Education in the period 1935-1985) can be regarded as the tuning fork regarding the aims of the science of education practised in that particular Faculty. The Faculty of Education of the PU for CHE celebrated a half-century of academic work in 1985. This article reports on an analysis of the views of the five deans who served (the last one is still serving) in the Faculty, on the aims and the task of the science of education. It was found that interalia one ideal was kept alive by all the deans: to practise education in a Scriptural/Christian way. Also, they all tried to either explain how Scriptural education (Pedagogics) works or what efforts should be con trived to ensure this form of scientific work. It was also found that certain developments in the views on the roles of norms and facts in the process of scientific work took place as the years went by and greater in sigh t was gained in the philosophy of (educational) science.